An investigation of the effects of FGFR2 and B7-H4 polymorphisms in breast cancer - Şamli, Hale; Imirzalioglu, Necat; Aktepe, Fatma; Icduygu, Fadime Mutlu; Orhan, Bulent; Ozturk, Kuyas Hekimler; Ozgoz, Asuman (Medknow, 2013)
Polymorphisms in FGFR2 are important markers for breast cancer susceptibility in the general population. CHEK2 and FGFR2 polymorphisms with known susceptibility alleles of BRCA1, BRCA2, PTEN, and TP53, can be investigated as potential modifiers of high penetrant risk alleles. Although the B7-H4 gene is highly expressed in many different tumors, there is one published study showing the association of polymorphisms with breast cancer. We aimed to investigate FGFR2 and B7-H4 polymorphisms in breast cancer in the Turkish community.In a group of 31 cases diagnosed with breast cancer and 30 healthy women with matched ages, the single-nucleotide polymorphisms (SNPs) rs1219648, rs2981582 in FGFR2 gene were identified by sequence analysis and the SNPs rs10754339, rs10801935, and rs3738414 in the B7-H4 gene were identified by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Statistical analysis was performed using SPSS.Although statistically not significant, the frequency of FGFR2 heterozygous polymorphisms in the group with breast cancer was detected to be higher. In the B7-H4 SNP rs10801935, polymorphic AA, and AG genotype distributions were found in higher frequencies in the breast cancer patients. In contrast to the results of a published study, the present study shows that B7-H4 rs3738414 polymorphism GG genotype was found in higher frequency in the control group than the breast cancer group and the result was statistically significant (P=0.018).Larger scale studies are necessary to determine the prevalence of these polymorphisms and association with breast cancer in Turkish community, as this study is the first study performed.
Keywords: Adult; Risk; Genotype; Turkey; Breast Neoplasms; Middle Aged; V-Set Domain-Containing T-Cell Activation Inhibitor 1; Polymorphism, Single Nucleotide; polymorphism; Breast cancer; B7-H4; Gene Frequency; FGFR2; Case-Control Studies; Humans; Female; Receptor, Fibroblast Growth Factor, Type 2; Alleles; Genetic Association Studies; Aged; 3. Good health